The unexpected influence of aryl substituents in N-aryl-3-oxobutanamides on the behavior of their multicomponent reactions with 5-amino-3-methylisoxazole and salicylaldehyde - Tkachenko, Volodymyr V.; Muravyova, Elena A.; Desenko, Sergey M.; Shishkin, Oleg V.; Shishkina, Svetlana V.; Sysoiev, Dmytro O.; Müller, Thomas J. J.; Chebanov, Valentin A. (Beilstein Journal of Organic Chemistry, 2014)
The switchable three-component reactions of 5-amino-3-methylisoxazole, salicylaldehyde and N-aryl-3-oxobutanamides under different conditions were studied and discussed. The unexpected influence of the aryl substituent in N-aryl-3-oxobutanamides on the behavior of the reaction was discovered. The key influence of ultrasonication and Lewis acid catalysts led to an established protocol to selectively obtain two or three types of heterocyclic scaffolds depending on the substituent in the N-aryl moiety.
Keywords: 5-amino-3-methylisoxazole; catalysis; chemoselectivity; heterocycle; multicomponent reaction; ultrasonication; salicylaldehyde

(untitled) - Světlik, J.; Veizerová, L.; Mayer, T. U.; Catarinella, M. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Grover, G. J.; Dzwonczyk, S.; McMullen, D. M.; Normandin, D. E.; Parham, C. S.; Sleph, P. G.; Moreland, S. (J. Cardiovasc. Pharmacol., 1995)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Atwal, K. S.; Rovnyak, G. C.; Kimball, S. D.; Floyd, D. M.; Moreland, S.; Swanson, B. N.; Gougoutas, J. Z.; Schwartz, J.; Smillie, K. M.; Malley, M. F. (J. Med. Chem., 1990)

PCT Int. Patent - Atwal, K. S.; Vaccaro, W.; Lloyd, J.; Finlay, H.; Yan, L.; Bhandaru, R. S.
Chem. Abstr. 2007, 135, 19660–19666.

(untitled) - Atwal, K. S.; Moreland, S. (Bioorg. Med. Chem. Lett., 1991)

(untitled) - Ryabukhin, S. V.; Plaskon, A. S.; Boron, S. Yu.; Volochnyuk, D. M.; Tolmachev, A. A. (Mol. Diversity, 2011)

(untitled) - Chebanov, V. A.; Muravyova, E. A.; Desenko, S. M.; Musatov, V. I.; Knyazeva, I. V.; Shishkina, S. V.; Shishkin, O. V.; Kappe, C. O. (J. Comb. Chem., 2006)

(untitled) - Gladkov, E.; Sirko, S.; Khanetskii, B.; Lukinova, E.; Desenko, S. (Chem. Pap., 2007)

(untitled) - Borisagar, M.; Joshi, K.; Ram, H.; Vyas, K.; Nimavat, K. (Acta Chim. Pharm. Indica, 2012)

(untitled) - Muravyova, E. A.; Desenko, S. M.; Rudenko, R. V.; Shishkina, S. V.; Shishkin, O. V.; Sen'ko, Y. V.; Vashchenko, E. V.; Chebanov, V. A. (Tetrahedron, 2011)

(untitled) - Gladkov, E. S.; Sirko, S. N.; Shishkina, S. V.; Shishkin, O. V.; Knyazeva, I. V.; Desenko, S. M.; Chebanov, V. A. (Monatsh. Chem., 2010)

(untitled) - Muravyova, E. A.; Tkachenko, V. V.; Desenko, S. M.; Sen’ko, Y. V.; Müller, T. J. J.; Vashchenko, E. V.; Chebanov, V. A. (ARKIVOC, 2013)

(untitled) - Chebanov, V. A.; Desenko, S. M. (Curr. Org. Chem., 2006)

(untitled) - Chebanov, V. A.; Gura, K. A.; Desenko, S. M. (Top. Heterocycl. Chem., 2010)

(untitled) - Světlik, J.; Veizerová, L.; Kettmann, V. (Tetrahedron Lett., 2008)

(untitled) - Jing, X.; Li, Z.; Pan, X.; Wang, Q.; Yan, C.; Zhu, H. (Synth. Commun., 2009)

(untitled) - Gorobets, N. Yu.; Sedash, Y. V.; Ostras, K. S.; Zaremba, O. V.; Shishkina, S. V.; Baumer, V. N.; Shishkin, O. V.; Kovalenko, S. M.; Desenko, S. M.; van der Eycken, E. V. (Tetrahedron Lett., 2010)

(untitled) - Světlík, J.; Kettmann, V. (Tetrahedron Lett., 2011)

(untitled) - Umarov, B. B.; Ishankhodzhaeva, M. M.; Khusenov, K. S.; Parpiev, N. A.; Talipov, S. A.; Ibragimov, B. T. (Russ. J. Org. Chem., 1999)

(untitled) - Chebanov, V. A.; Desenko, S. M. (Chem. Heterocycl. Compd., 2012)

(untitled) - Sakhno, Y. I.; Shishkina, S. V.; Shishkin, O. V.; Musatov, V. I.; Vashchenko, E. V.; Desenko, S. M.; Chebanov, V. A. (Mol. Diversity, 2010)

(untitled) - Chebanov, V. A.; Sakhno, Y. I.; Desenko, S. M. (Ultrason. Sonochem., 2012)

(untitled) - Chebanov, V. A.; Saraev, V. E.; Shishkina, S. V.; Shishkin, O. V.; Musatov, V. I.; Desenko, S. M. (Eur. J. Org. Chem., 2012)

Multicomponent Heterocyclizations with Controlled Selectivity. Reactions of Carbonyls with Nitrogen-containing Mono-, Bi- and Polynucleophiles - Chebanov, V.; Desenko, S. (LAP LAMBERT Academic Publishing, 2011)

Azaheterocycles Based on α,β-Unsaturated Carbonyls - Chebanov, V. A.; Desenko, S. M.; Gurley, T. W. (Springer, 2008)

(untitled) - Cepanec, I.; Litvić, M.; Filipan-Litvić, M.; Grüngold, I. (Tetrahedron, 2007)

(untitled) - Adibi, H.; Samimi, H. A.; Beygzadeh, M. (Catal. Commun., 2007)

(untitled) - Zefirov, N. S.; Palyulin, V. A.; Dashevskaya, E. E. (J. Phys. Org. Chem., 1990)